HER2 assessment by bright‐field dual in situ hybridization in cell blocks of recurrent and metastatic breast carcinoma. Issue 11 (22nd September 2019) - Edelweiss, Marcia; Sebastiao, Ana Paula Martins; Oen, Handy; Kracun, Mihaela; Serrette, Rene; Ross, Dara S.
Abstract : Background: Breast cancer recurrences or metastases often are diagnosed using cytology material. Cell blocks (CBs) with adequate cellularity are crucial for the determination of accurate hormonal and human epidermal growth factor receptor 2 (HER2) status and to guide treatment. In the current study, the authors evaluated the concordance of HER2 status between bright‐field dual in situ hybridization (DISH), fluorescence in situ hybridization (FISH), and HER2 immunohistochemistry (IHC) performed on formalin‐fixed CBs of recurrent and metastatic breast cancers. Methods: The authors searched for patients who had breast carcinoma recurrences or metastases diagnosed between 2010 and 2018 by fine‐needle aspiration or by the drainage of body cavity fluids with HER2 IHC and/or FISH performed on formalin‐fixed CBs. Cases with adequate tumor cellularity (>50 cells) were selected. HER2 DISH was performed on all CBs. HER2 status of the primary breast carcinoma was recorded. Results: Formalin‐fixed CBs were identified from 30 patients with breast cancer recurrences and metastases in axillary lymph nodes (LNs) (5 patients), mediastinal LNs (8 patients), internal mammary LNs (1 patient), supraclavicular LNs (2 patients), portocaval LNs (1 patient), chest wall (3 patients), pleural fluid (3 patients), bone (4 patients), liver (2 patients), and lung (1 patient). All cases had HER2 IHC performed at the study institution and were scored by breast pathologists according to the American Society of Clinical Oncology/College of American Pathologists guidelines. The HER2 DISH results demonstrated 100% concordance (30 of 30 cases) with the concurrent IHC and/or FISH. Conclusions: All methods of HER2 evaluation were found to accurately identify the amplification status. DISH can be used in tandem with IHC as a reflex assay instead of FISH and is an efficient and reliable method with which to determine HER2 amplification in formalin‐fixed CBs. Abstract : Dual in situ hybridization (DISH) can be used in tandem with immunohistochemistry as a reflex assay instead of fluorescence in situ hybridization (FISH) to determine human epidermal growth factor receptor 2 amplification in formalin‐fixed cell blocks. DISH offers advantages over FISH in cell blocks, including the ability to archive slides and the simultaneous assessment of morphology and gene copy number using a light microscope.